2012
DOI: 10.1021/ie201908s
|View full text |Cite
|
Sign up to set email alerts
|

What Reacts with What in Bisphenol A Polycarbonate/Silicon Rubber/Bisphenol A Bis(diphenyl phosphate) during Pyrolysis and Fire Behavior?

Abstract: The pyrolysis and flame retardancy of a bisphenol A polycarbonate/silicon rubber/bisphenol A bis(diphenyl phosphate) (PC/SiR/BDP) blend were investigated and compared to those of PC/BDP and PC/SiR. The impact modifier SiR consists mainly of poly(dimethylsiloxane) (PDMS > 80 wt %). The pyrolysis of PC/SiR/BDP was studied by thermogravimetry (TG), TG–FTIR to analyze the evolved gases, and a Linkam hot stage cell within FTIR as well as 29Si NMR and 31P NMR to analyze the solid residue. The fire performance was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…The results confirmed that the addition reaction between CC bonds in MVC and PH bonds in DOPO had happened. The other three typical absorption bands (at 1080 cm −1 , associated with the vibrations of SiOSi; at 797 cm −1 , corresponding to the SiC bond; and at 904 cm −1 , representing the PO bond in phosphaphenanthrene, all appeared in the spectrum of MVC‐DOPO, further testifying that MVC‐DOPO had been synthesized successfully.…”
Section: Resultsmentioning
confidence: 81%
“…The results confirmed that the addition reaction between CC bonds in MVC and PH bonds in DOPO had happened. The other three typical absorption bands (at 1080 cm −1 , associated with the vibrations of SiOSi; at 797 cm −1 , corresponding to the SiC bond; and at 904 cm −1 , representing the PO bond in phosphaphenanthrene, all appeared in the spectrum of MVC‐DOPO, further testifying that MVC‐DOPO had been synthesized successfully.…”
Section: Resultsmentioning
confidence: 81%
“…The spectrum of EP dominated the spectra of all composite specimens by showing the characteristic peaks for H 2 O (3400–4000 and 1700–2200 cm −1 ), free OH (3649 cm −1 ), C aromatic‐H (3035, 831, 746 cm −1 ), CH 4 (3016 cm −1 ), C aromatic &bond;C aromatic stretch (1606, 1508 cm −1 ), C aliphatic‐H (2974, 2935, 2881, 1460 cm −1 ), CO 2 (2359 cm −1 ), CHO (2814 cm −1 ), lactones (1797, 1772 cm −1 ), C&dbond;O (1716 cm −1 ), C&bond;H of bisphenol A (1331, 1176 cm −1 ), RC&dbond;CH 2 (887 cm −1 ), and C&bond;O and C&bond;H of bisphenol A (1259 cm −1 ). Most peaks of the spectra are attributed to bisphenol A, which is the main part of DGEBA resin . Bisphenol A fragment dominates the FTIR spectrum of EP pyrolysis gas, as it did those of all the other materials investigated.…”
Section: Resultsmentioning
confidence: 93%
“…All spectra were dominated by the spectrum of EP, showing the release of H 2 O (4000 cm À1 to 3400 cm À1 and 2200 cm À1 to 1700 cm À1 ), free OH (3649 cm À1 ), C aromatic -H (3035 cm À1 , 831 cm À1 , 746 cm À1 ), CH 4 (3016 cm À1 ), C aromatic -C aromatic stretch (1606 cm À1 , 1508 cm À1 ), C aliphatic -H (2974 cm À1 , 2935 cm À1 , 2881 cm À1 , 1460 cm À1 ), CO 2 (2359 cm À1 ), CHO (2814 cm À1 ), lactones (1797 cm À1 , 1772 cm À1 ), C]O (1716 cm À1 ), C-H of bisphenol A (1331 cm À1 , 1176 cm À1 ), RC]CH 2 (887 cm À1 ), C-O and C-H of bisphenol A (1259 cm À1 ). Most peaks of the spectra are associated with bisphenol-A, 36 which is part of the DGEBA resin component. 1,10 Bisphenol A actually dominates the spectrum of EP, as it does for all of the other investigated materials.…”
Section: Pyrolysis: Mass Evolved Gas and Residue Analysismentioning
confidence: 99%